2010
DOI: 10.1137/090757010
|View full text |Cite
|
Sign up to set email alerts
|

Fast Access to Distributed Atomic Memory

Abstract: Abstract. We study efficient and robust implementations of an atomic read-write data structure over an asynchronous distributed message-passing system made of reader and writer processes, as well as a number of servers implementing the data structure. We determine the exact conditions under which every read and write involves one round of communication with the servers. These conditions relate the number of readers to the tolerated number of faulty servers and the nature of these failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 18 publications
2
50
0
Order By: Relevance
“…Moreover, the reader in [9] needs to write (i.e., modify the objects' state) as dictated by the lower bound of [12] which showed that every atomic read must write into at least t objects. [10] extends the result of [9] to the Byzantine failure model assuming authenticated (i.e., digitally signed) data and established the impossibility of fast crash-tolerant multiwriter multi-reader (MWMR) atomic register implementations. This result is in line with classical MWMR implementations such as [22] that have read/write latency of at least 2 rounds.…”
Section: Related Workmentioning
confidence: 72%
“…Moreover, the reader in [9] needs to write (i.e., modify the objects' state) as dictated by the lower bound of [12] which showed that every atomic read must write into at least t objects. [10] extends the result of [9] to the Byzantine failure model assuming authenticated (i.e., digitally signed) data and established the impossibility of fast crash-tolerant multiwriter multi-reader (MWMR) atomic register implementations. This result is in line with classical MWMR implementations such as [22] that have read/write latency of at least 2 rounds.…”
Section: Related Workmentioning
confidence: 72%
“…. , reg(m) be the arrays received at the previous line; (11) for Algorithm implementing the operation snapshot(): client side As previously, this algorithm is decomposed in two parts. The part described at lines 7-13 is executed by the invoking process p i (client), while lines 16-17 are executed by all processes (in their server role).…”
Section: Local Variables Initializationmentioning
confidence: 99%
“…Many constructions of atomic read/write registers on top of message-passing systems have been proposed (e.g., [3,7,11,20,22,23,24,25] to cite a few). They differ in the type and the number of failures they tolerate, the number of messages they need to implement a read or a write operation, the size of control information carried by these implementation messages, and the time complexity of each operation [27].…”
Section: Introductionmentioning
confidence: 99%
“…. Proof: G v must collect a quorum of proposals for a sequence seq to generate it (lines [12][13][14]. Each server i ∈ v makes a single initial proposal (line 1) and updates it only by processing proposals from other server of v (lines 8 and 10).…”
Section: Lemma 1 (Weak Accuracy) Consider the View Generatorsmentioning
confidence: 99%